Determinación de la susceptibilidad de cuarenta materiales de Arroz (oryza sativa l.) a “meloidogyne graminicola - Reyes Peñafiel, Isaías Benito (2013)
The root knot nematode, Meloidogyne graminicola is the main cause of the most common infestation in rice roots in Ecuador. It was identified in 1987 and today has been spread in the all rice-growing areas of the country. Knowing the importance of crop in our country this research was conducted to determine the degree of susceptibility of 40 rice materials directed inoculation, with the aim of having promising genotypes the rice with resistance to root-knot nematode, owing that all the Commercial materials are susceptible to M. graminicola. This research was conducted in the greenhouse the Nematology Department in South Coast Experimental Station, at Autonomous National Institute for Agricultural Research (INIAP), located in the Durán-Tambo Road, Canton Yaguachi; Guayas Province..........